Berdaya dalam Kerja: Menelusuri Dimensi Pemberdayaan Psikologis Gen Z - Soerjoatmodjo, Gita Widya Laksmini (Jurnal Riset Psikologi, 2025)
Abstract. Generation Z has become a dominant force in today’s workforce, yet many organizations still lack a full understanding of this generation’s values and expectations. Gen Z seeks work experiences that are meaningful, empowering, and offer space for personal growth. Psychological empowerment consists of four dimensions: meaning, competence, self-determination, and impact. This study employed a quantitative approach using a survey design involving 465 Gen Z employees from various industrial sectors in Indonesia, aiming to identify the most prominent dimensions of psychological empowerment within this group. The analysis revealed significant differences (p  < 0.001) among the four dimensions, with competence and meaning emerging as the highest-rated, while self-determination and impact were rated the lowest. These findings indicate that although Gen Z employees are confident in their competence and find their work meaningful, they often do not feel autonomous or perceive that their contributions make a real impact on the organization. Therefore, it is essential for organizations not only to support competence but also to provide space for autonomy and recognize employees’ contributions. At the same time, Gen Z can also develop the ability to articulate their work preferences constructively. Abstrak. Generasi Z merupakan kekuatan dominan di dunia kerja, namun banyak organisasi belum sepenuhnya memahami nilai dan ekspektasi generasi ini. Gen Z mendambakan pengalaman kerja yang bermakna, memberdayakan, dan memberi ruang untuk berkembang. Pemberdayaan psikologis terdiri atas empat dimensi: makna, kompetensi, determinasi diri, dan dampak. Studi ini menggunakan pendekatan kuantitatif dengan desain survei terhadap 465 pegawai Gen Z di berbagai sektor industri di Indonesia, dan bertujuan mengidentifikasi dimensi pemberdayaan psikologis yang paling menonjol pada kelompok ini. Hasil analisis menunjukkan perbedaan yang signifikan (p < 0.001) antar dimensi, dengan kompetensi sebagai dimensi tertinggi, disusul oleh makna, sementara determinasi diri dan dampak merupakan dimensi dengan skor terendah.Temuan ini mengindikasikan bahwa meskipun pegawai Gen Z percaya diri dengan kompetensinya dan menjalankan pekerjaan yang bermakna, mereka belum merasa memiliki ruang otonomi maupun dampak nyata terhadap organisasi. Oleh karena itu, penting bagi organisasi untuk tidak hanya mendukung kompetensi, tetapi juga menciptakan ruang bagi otonomi serta memberikan pengakuan atas kontribusi mereka. Di sisi lain, Gen Z juga perlu mengembangkan kemampuan artikulatif untuk mengekspresikan preferensi cara kerja secara konstruktif.